Therapeutic Angiogenesis by Autologous Bone Marrow Cell Implantation for Refractory Chronic Peripheral Arterial Disease Using Assessment of Neovascularization by 99mTc-Tetrofosmin (TF) Perfusion Scintigraphy - Masaaki Miyamoto M.D.; Masahiro Yasutake; Hitoshi Takano; Hiromichi Takagi; Gen Takagi; Hiroshi Mizuno; Shinichiro Kumita; Teruo Takano (Cell Transplantation, 2004)
We investigated efficacy and safety of implantation of autologous bone marrow mononuclear cells plus platelets, including endothelial progenitor cells (EPCs), for recovering refractory chronic peripheral arterial disease (PAD) using visual and quantitative analyses by 99m Tc-tetrofosmin (TF) perfusion scintigraphy, and also investigated various quantitative assessments objectively. We performed 12 consecutive cases and 19 limbs and hands with severe chronic PAD that were almost Fontaine class IV (11/12 cases, about 92%) in this trial. This treatment was very effective in relieving severe pain of PAD, especially for Buerger's disease. We used a visual analog scale (VAS) for measurement of pain level. The maximum pain level before implantation was 66.5 ± 5.0 mm, and it decreased to 12.1 ± 2.2 mm after implantation (p < 0.001). Rest pain in legs and fingers was resolved in 11 cases (11/12 cases, 92%). All patients could measure pain-free walking time on a treadmill, which improved remarkably (140 ± 53 s before implantation vs. 451 ± 74 s after implantation, p = 0.034). Resting ankle brachial pressure index (ABI) in legs implanted with bone marrow mononuclear cells was also improved (0.65 ± 0.08 before implantation vs. 0.73 ± 0.07 after implantation, p = 0.055). According to 99m Tc-TF perfusion scintigraphy, the proximal area (region from knee to ankle) was 1.32 ± 0.10 before implantation versus 1.56 ± 0.11 after implantation (p = 0.007). 99m Tc-TF perfusion scintigraphy in the distal area (region from ankle to end of toes, or from wrist to end of fingers) was 0.79 ± 0.06 before implantation versus 0.83 ± 0.06 after implantation (p = 0.29). Ischemic legs and hands that were injected showed increased perfusion blood flow. 99m Tc-TF perfusion scintigraphy was effective to estimate visual and quantitative analysis of collateral vessels in neovascularization. We were successful with this new treatment for the most severe, chronic PAD that was not curable by any of the current treatments. Thus, this therapeutic angiogenesis could be a new strategy for saving severe ischemic limbs and hands.